Coaching for the pediatric anesthesiologist: Becoming our best selves. Issue 1 (7th November 2020) - Schwartz, Jamie McElrath; Wittkugel, Eric; Markowitz, Scott D.; Lee, Jennifer K.; Deutsch, Nina
Abstract: Anesthesiologists must balance demanding clinical workloads with career development goals. Leadership, conflict management, and other skills can improve medical outcomes, reduce stress at work, and increase career satisfaction. However, Medicine in general and Anesthesiology in particular have not traditionally emphasized physician growth in these areas. Coaching utilizes concepts from psychology, adult learning, and adult development theory to support an individual in personal and professional growth through inquiry, reflection, and shared discovery. This manuscript reviews the history and evidence basis for coaching, differentiates coaching from traditional mentorship, and presents some constructs of coaching and working with a coach. An example of a successful pilot program to disseminate coaching skills and support leadership growth among anesthesiologists, the Women's Empowerment and Leadership Initiative within the Society for Pediatric Anesthesia, is described.